Measuring both systems of reasoning: a study of the predictive capacity of a new version of the Rational-Experiential Inventory (European Journal of Education and Psychology, 2012)
Previous research on the Rational-Experiential Inventory (REI; Epstein, Pacini,  Denes-Raj and Heier, 1996) has produced inconsistent results concerning its  predictive validity with specific reasoning tasks. To evaluate the predictive  capacity of the REI in greater detail we used ten tasks requiring different types of reasoning (e.g., deductive and probabilistic). The latest version of the REI (Pacini and Epstein, 1999) was adapted to Spanish and answered by 120 participants. Findings suggest  that thinking styles of processing as measured by the REI reflect the existence of  individual differences, but that its predictive capacity is limited to some particular  reasoning tasks. Some explanations for these limitations are discussed within the  context of dual-reasoning theories.